Study protocol: evaluation of sheds for life (SFL): a community-based men's health initiative designed "for shedders by shedders" in Irish Men's sheds using a hybrid effectiveness-implementation design - Aisling McGrath; Niamh Murphy; Noel Richardson (BMC, 2021)
Abstract Background Men's Sheds ("Sheds") offer a unique opportunity to reach a captive audience of "hard-to-reach" men. However, attempts to engage Sheds in structured health promotion programmes must respect the ethos of Sheds as highly variable, autonomous, non-structured spaces. This paper captures the key methodologies used in "Sheds for Life' (SFL), a men's health initiative tailored to the Shed setting. Methods A hybrid effectiveness-implementation study design is used to test effectiveness and implementation outcomes across multiple levels (participant, provider, organisational and systems levels). A dynamic, iterative and collaborative process seeks to address barriers and translation into the real world context. Using a community-based participatory research approach and guided by established implementation frameworks, Shed members ('Shedders') assume the role of key decision makers throughout the evaluation process to promote the systematic uptake of SFL across Shed settings. The protocols pertaining to the development, design and implementation of SFL and the evaluation of impact on participants' health and wellbeing outcomes up to 12 months are outlined. Conclusions There is a dynamic interplay between the intervention characteristics of SFL and the need to assess and understand the diverse contexts of Sheds and the wider implementation environment. A pragmatic and context-specific design is therefore favoured over a tightly controlled efficacy trial. Documenting the protocols used to evaluate and implement a complex multi-level co-developed intervention such as SFL helps to inform gender-specific, community-based men's health promotion and translational research more broadly. Trial registration This study has been retrospectively registered with the 'International Standard Randomised Controlled Trial Number' registry ( ISRCTN79921361 ) as of the 5th of March 2021.